Ivacaftor, a Cystic Fibrosis Transmembrane Conductance Regulator Potentiator, Enhances Ciprofloxacin Activity Against Pseudomonas aeruginosa. Issue 2 (March 2019) - Cho, Do-Yeon; Lim, Dong Jin; Mackey, Calvin; Skinner, Daniel; Zhang, Shaoyan; McCormick, Justin; Woodworth, Bradford A.
Background: Methods to improve the clinical efficacy of currently available antibiotics against multidrug resistant bacteria in cystic fibrosis (CF) chronic rhinosinusitis (CRS) are greatly needed. Ivacaftor, a cystic fibrosis transmembrane conductance regulator potentiator, was recently identified as having potentially beneficial off-target effects as a weak inhibitor of bacterial DNA gyrase and topoisomerase IV. The objective of the current study is to evaluate whether ivacaftor enhances the antimicrobial activity of ciprofloxacin against Pseudomonas aeruginosa . Methods: The planktonic growth of the PAO-1 strain of P. aeruginosa was studied in the presence of ciprofloxacin and/or ivacaftor. Effects were measured according to optical density of cultured PAO-1 at 600 nm. For a static PAO-1 biofilm assay, the PAO-1 strain was inoculated and cultured for 72 h in the presence of the drugs. Formed PAO-1 biofilms were quantified by crystal violet staining and imaged with confocal laser scanning microscopy (CLSM) and scanning electron microscopy (SEM). Results: PAO-1 growth was significantly reduced in the presence of ivacaftor (8 or 16 µg/mL) and ciprofloxacin (0.02 or 0.05 µg/mL) compared to ciprofloxacin alone ( P < .001). Similarly, ivacaftor (8 or 16 µg/mL) showed a significant reduction of PAO-1 biofilms when treated with 0.05 µg/mL of ciprofloxacin. Significant synergism was noted between ciprofloxacin and 16 µg/mL of ivacaftor ( P < .0001) in reducing planktonic growth and biofilm formation. Quantitative measurements with crystal violet staining were correlated to CLSM and SEM images. Conclusion: Ivacaftor enhanced ciprofloxacin's antimicrobial activity against P. aeruginosa . Further studies evaluating the efficacy of ivacaftor/ciprofloxacin combination for P. aeruginosa for CF CRS are warranted.